2019
DOI: 10.35940/ijeat.a2654.109119
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Factors Influencing Customers’ Purchase Intention Towards Online SNSs Sellers

Abstract: Business on social commerce has become trending due to facilities provided by Social Networking Sites (SNSs). Trust and reputations are the de facto challenges that influence social commerce customers’ purchase intention, an area of research that is sparse in the literature. The objective of this study is to identify different factors that may influence customers’ purchase intention particularly in transactions with online SNSs sellers. The study collected 397 responses collected from the online survey were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Therefore, they become intend to buy the product. The findings of this study are in line with the findings of previous studies (Khalid, 2019;Oeawpanich, 2018;Ramona et al, 2019) that show that social media affects purchase intention.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, they become intend to buy the product. The findings of this study are in line with the findings of previous studies (Khalid, 2019;Oeawpanich, 2018;Ramona et al, 2019) that show that social media affects purchase intention.…”
Section: Discussionsupporting
confidence: 92%
“…The results of Wani et al's study (2016) found that a positive attitude towards eWOM and previous beneficial experiences were the main drivers of Indian buyers' online purchase intention. Ramona et al, (2019) show that eWOM content affects consumers' intentions to make online purchases. Avriyanti et al, (2018) show that eWOM significantly influences consumer intentions to purchase Zalora's online shop products.…”
Section: Theoretical Reviewmentioning
confidence: 98%
See 1 more Smart Citation